Intravenous Implanted Neural Stem Cells Migrate to Injury Site, Reduce Infarct Volume, and Improve Behavior after Cerebral Ischemia - Shen, Chiung-Chyi; Lin, Chen-Huan; Yang, Yi-Chin; Chiao, Ming-Tsang; Cheng, Wen-Yu; Ko, Jiunn-Liang (Current Neurovascular Research, 2010)
Stroke represents one of the leading causes of death and disability in humans, but despite intense research, only a few options exist for the treatment of stroke-related infarction of brain tissue. Thus far, in experimental strokes, cell therapy appears to partly reverse some behavioral deficits. However, the mechanisms of action remain uncertain as most studies reveal only little, if any, evidence for neuronal replacement and observed behavioral improvements. This present study was performed to test rodent fetus forebrain derived neural stem cells (NSCs) implantation into rats subjected to suture-induced middle cerebral artery occlusion (MCAO). Efficacy of cell therapy was studied regarding behavior recovery, infarct volume, and protection possibility of related molecular mechanisms. Here, we show that grafted cells can home in on damaged regions by MCAO and significantly improve behavior of ischemic rats. Infarct volumes and brain atrophy were diminished after grafted NSCs treatment. Furthermore, we detected inflammation related molecules such as COX-2 and IL-1β and found that grafted NSCs treatment after ischemic stroke could repress expression of inflammation molecular protein levels. We also detected protein levels of heat shock protein 27 (HSP27) as a protective protein against apoptosis. The results showed that grafted NSCs treatment induced the protein level of HSP27 and down-regulated activity of caspase-3 compared with the vehicle control. Our results demonstrate that transplanted NSCs provide benefits in behavioral function recovery after MCAO and increase neuroprotection whilst repressing inflammatory destruction. These data reveal another essential explanation of cellular transplantation therapy in damage recovery from ischemic stroke and offer new therapeutic possibilities.
Keywords: neural stem cell